The Monetary and Non-Monetary Impacts of Prefabrication on Construction: The Effects of Product Modularity - Krishna Chauhan; Antti Peltokorpi; Rita Lavikka; Olli Seppänen (Buildings, 2022)
Prefabrication is rapidly increasing in construction, and previous research has identified various impacts of prefabrication on projects. Modular product architecture is a great enabler for prefabrication; however, practitioners would benefit from more explicit knowledge on the impacts of prefabricated product types with different levels of product modularity. This study investigates the connection between the modularity level and the monetary and non-monetary impacts of prefabricated products. First, the literature on prefabrication and modularity is used to form three propositions which are related to product modularity and the benefits of prefabrication. The level of modularity is considered with two dimensions: the proportion of modules and the module description detail. Second, four prefabricated products are analyzed to test the propositions. The analysis revealed that (1) the level of modularity adopted in the product is directly proportional to the benefits. More specifically, (2) a higher proportion of modules in a project product contributes to higher cost-benefits. On the other hand, (3) prefabricated products with highly detailed module descriptions seem to lead to higher non-monetary benefits, such as better ergonomics and work satisfaction. The study reveals new empirical evidence on the relationship between product modularity and the benefits of prefabricated products. Cost-benefit analysis revealed that even though some prefabricated products could have higher direct costs, the total cost can still be lower than conventional construction when also considering the indirect benefits. Practitioners can utilize the findings when selecting modular and prefabricated products that best fulfil their project objectives.